2013
DOI: 10.1517/13543776.2013.827662
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase inhibitors: a patent review (2008 – 2012)

Abstract: Key events that stimulated the search of IDO inhibitors are presented. To date, however, the number of available scaffolds remains limited with only one confirmed inhibitor (from Incyte Corp.) in the clinic. Major challenges in the search for IDO inhibitors are discussed as well as the relevance of selectivity of IDO inhibition versus inhibition of tryptophan 2,3-dioxygenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…immunocompetent mice 9 and a dose-dependent reduction of kynurenine levels in patients with cancer in a phase I study. 10 INCB024360 is currently evaluated in phase II clinical trials as a single agent in ovarian cancer and in combination with the CTLA-4 antagonist ipilimumab in metastatic melanoma, clearly showing the potential of IDO1 inhibitors as a treatment option for cancer. 10 Similar to IDO1, expression of TDO by immunogenic mouse tumor cells prevented their rejection by preimmunized mice, and the effect could be reverted with an inhibitor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…immunocompetent mice 9 and a dose-dependent reduction of kynurenine levels in patients with cancer in a phase I study. 10 INCB024360 is currently evaluated in phase II clinical trials as a single agent in ovarian cancer and in combination with the CTLA-4 antagonist ipilimumab in metastatic melanoma, clearly showing the potential of IDO1 inhibitors as a treatment option for cancer. 10 Similar to IDO1, expression of TDO by immunogenic mouse tumor cells prevented their rejection by preimmunized mice, and the effect could be reverted with an inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…10 INCB024360 is currently evaluated in phase II clinical trials as a single agent in ovarian cancer and in combination with the CTLA-4 antagonist ipilimumab in metastatic melanoma, clearly showing the potential of IDO1 inhibitors as a treatment option for cancer. 10 Similar to IDO1, expression of TDO by immunogenic mouse tumor cells prevented their rejection by preimmunized mice, and the effect could be reverted with an inhibitor. 11 Moreover, TDO is overexpressed in brain tumors, where it supports tumor growth and immune evasion by maintaining intratumoral kynurenine levels that activate the aryl hydrocarbon receptor and promote the generation of immune-suppressive T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since removal of the two carbonyl groups has a detrimental effect on the inhibition potency of the chlorinated derivatives (see 5,6, and 16), we retained the C2 carbonyl group and explored the effect of substitutions at the C3 position alone. As before, the effect of C3 substitutions was assessed in the presence and absence of chlorines.…”
Section: Substitutions At C3mentioning
confidence: 99%
“…Due to the early identification of IDO1 as an enzyme with immunomodulatory function and its broad expression in the body, it became the main target for drug discovery. Many years of research have revealed a large number of IDO1 inhibitors with affinities that reach the low nanomolar region 1,[5][6][7][8] . Of these, the most promising candidate, known as INCB024360, is currently under investigation in clinical trials 9 .…”
Section: Introductionmentioning
confidence: 99%
“…12) Although there were many basic studies on the IDO1 and IDO1 inhibitors, the studies on high throughput virtual screening (HTVS) for IDO1 inhibitors remained very few and most of them were done before 2012. 13,14) Here, we designed an effective HTVS protocol combining both pharmacophore modeling and molecular docking with the help of many basic studies after 2012 such as structure-activity relationship (SAR), binding modes and fresh released crystal structure.…”
mentioning
confidence: 99%